Systematic literature review of long-term efficacy data for topical psoriasis treatments. (19th May 2022) - Bark, Claire; Brown, Chloe; Svangren, Per
Abstract: Objective: To identify long-term efficacy evidence that supports use of topical therapies as regular maintenance therapy in the prevention of psoriasis relapse. Methods: A systematic literature review identified clinical trials and observational studies that reported efficacy outcomes for topical psoriasis therapies with treatment durations of at least 12 weeks. For therapies with long-term data, the approved treatment schedules in product labels were reviewed. Results: Forty-six studies with at least 12-week efficacy outcomes were identified. Eight randomized controlled trials and six observational studies or single-arm open-label studies reported efficacy data for >12-week treatment periods. Most studies used treatment regimens that reflect current standard of care of repeated treatment of relapses. The PSO-LONG study is the only identified randomized controlled trial to have compared regular proactive maintenance use of a topical treatment (calcipotriol/betamethasone foam) with reactive management in response to psoriasis relapses. Conclusions: Limited high-quality long-term efficacy data are available for topical psoriasis therapies. While some product labels mention clinical experience of up to 12 months, they do not provide specific recommendations on the optimal long-term regimen. Calcipotriol/betamethasone foam is the only treatment for which the approved label allows either reactive treatment of relapse or regular (twice weekly) maintenance use.